Barriers and facilitators to using ophthalmic clinical health services following school vision screening: a mixed-methods study - Jingjing Wang; Xiangui He; Jingwen Hu; Huijing Shi; Pingping Lyu; Jiaojiao Shi (BMJ Publishing Group, 2024)
Objective To identify determinants of the utilisation of ophthalmic clinical health services among students who failed school vision screening.Methods This study employed a sequential explanatory mixed methods design, underpinned by Andersen's Behavioural Model of Health Service Utilisation. Data were initially gathered through interviews with 27 stakeholders-comprising 5 ophthalmologists, 7 community doctors, 7 public health professionals and 8 teachers. The qualitative insights informed the construction of a questionnaire, which subsequently garnered responses from 6215 participants. Qualitative data underwent thematic analysis with NVivo V.12, while quantitative data were analysed using multivariable multinomial logistic regression in SAS V.9.4. Data integration was performed using the Pillar Integration Process for a deductive, evidence-based synthesis of findings.Results The research revealed that students attending vision demonstration schools and receiving encouragement from schools or communities to access clinical ophthalmic services demonstrated higher adherence to referral (OR=1.66, 95% CI 1.30 to 2.12; OR=1.54, 95% CI 1.33 to 1.80). Conversely, older students and those from higher-income families exhibited lower adherence rates (OR=0.31, 95% CI 0.23 to 0.44; OR=0.34, 95% CI 0.25 to 0.46). Moreover, students with less urgent medical needs were more likely to adhere to referrals compared with those needing immediate referrals (OR=1.24, 95% CI 1.06 to 1.45).Four pillars emerged: (a) adherence decreased with age, (b) financial constraints did not pose an obstacle, (c) public health services played a critical role, (d) referral urgency did not linearly correlate with adherence.Conclusion The utilisation of ophthalmic clinical health services following vision screening failure in students is significantly influenced by public health services provided by schools or communities, such as prompting those with abnormal screening results to access ophthalmic clinical health services.